1984
DOI: 10.1007/bf00053803
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high CO2 levels on surface temperature and atmospheric oxidation state of the early Earth

Abstract: One-dimensional radiative-convective and photochemical models are used to examine the effects of enhanced CO2 concentrations on the surface temperature of the early Earth and the composition of the prebiotic atmosphere. Carbon dioxide concentrations of the order of 100-1000 times the present level are required to compensate for an expected solar luminosity decrease of 25-30%, if CO2 and H2O were the only greenhouse gases present. The primitive stratosphere was cold and dry, with a maximum H2O volume mixing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
185
3
1

Year Published

1987
1987
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(191 citation statements)
references
References 67 publications
2
185
3
1
Order By: Relevance
“…However, improvements to the treatment of collision-induced absorption by carbon dioxide molecules have shown a decrease in the amount of warming possible by atmospheric CO 2 (Wordsworth et al 2010). In fact, the calculations by Wordsworth et al (2010) find that a 3 bar CO 2 atmosphere may be as much as 10 K cooler in their improved treatment of collision-induced absorption than the earlier model by Kasting et al (1984). This decrease in the expected amount of warming from atmospheric CO 2 outweighs any of the other improvements made to these radiative transfer calculations, so our calculations here can be considered as an overestimation of the greenhouse effect realizable by a dense CO 2 -H 2 O atmosphere.…”
Section: Methods: Energy Balance Model For Early Marsmentioning
confidence: 97%
“…However, improvements to the treatment of collision-induced absorption by carbon dioxide molecules have shown a decrease in the amount of warming possible by atmospheric CO 2 (Wordsworth et al 2010). In fact, the calculations by Wordsworth et al (2010) find that a 3 bar CO 2 atmosphere may be as much as 10 K cooler in their improved treatment of collision-induced absorption than the earlier model by Kasting et al (1984). This decrease in the expected amount of warming from atmospheric CO 2 outweighs any of the other improvements made to these radiative transfer calculations, so our calculations here can be considered as an overestimation of the greenhouse effect realizable by a dense CO 2 -H 2 O atmosphere.…”
Section: Methods: Energy Balance Model For Early Marsmentioning
confidence: 97%
“…The model is originally based on the one described by Kasting et al (1984a) and Kasting et al (1984b). Further developments are described by e.g.…”
Section: General Model Descriptionmentioning
confidence: 99%
“…Kasting et al 1984;Kasting & Brown 1998) has shown that rainout of photochemically produced oxidants and reductants is also important in the atmospheric redox balance. Indeed, rainout of oxidants such as H 2 O 2 and H 2 SO 4 becomes significant at atmospheric O 2 levels that are substantially lower than those shown in figure 7b.…”
Section: Possible Cause Of the Mid-archaean Glaciationsmentioning
confidence: 99%